2008
DOI: 10.3168/jds.2008-1028
|View full text |Cite
|
Sign up to set email alerts
|

Short-Day Photoperiod Increases Milk Yield in Cows with a Reduced Dry Period Length

Abstract: Exposure of cows to a short-day photoperiod (SDPP; 8 h light:16 h dark) during a 60-d dry period increases milk yield in the subsequent lactation compared with cows exposed to a long-day photoperiod (LDPP; 16 h light:8 h dark). Whereas the traditional recommendation for dry period length is 60 d, recent studies indicate that the dry period length can be reduced without depressing the yield in the next lactation. However, the optimal duration of the dry period appears to be between 40 and 60 d, because fewer th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 16 publications
7
28
1
Order By: Relevance
“…The milk yield response to LDPP during lactation averages around 2.5 kg/cow per d and becomes apparent after approximately 4 wk of exposure to extended light. Recent studies indicate that dry cows do not increase milk yield in the next lactation with only 21 d of exposure to SDPP, whereas a 35-d exposure to SDPP is sufficient to produce such a response in the next lactation (Reid et al, 2004;Velasco et al, 2006). Collectively, these studies support the concept that milk yield in cattle is greatly affected by varying the photoperiod exposure during the lactation cycle.…”
Section: Photoperiod Effects On Lactationmentioning
confidence: 68%
“…The milk yield response to LDPP during lactation averages around 2.5 kg/cow per d and becomes apparent after approximately 4 wk of exposure to extended light. Recent studies indicate that dry cows do not increase milk yield in the next lactation with only 21 d of exposure to SDPP, whereas a 35-d exposure to SDPP is sufficient to produce such a response in the next lactation (Reid et al, 2004;Velasco et al, 2006). Collectively, these studies support the concept that milk yield in cattle is greatly affected by varying the photoperiod exposure during the lactation cycle.…”
Section: Photoperiod Effects On Lactationmentioning
confidence: 68%
“…The effect in cattle is dependent on the duration of treatment because cows that were exposed to SDPP for only the final 21 d of the dry period did not exhibit the improvement in milk yield in the subsequent lactation (Reid et al, 2004). However, Velasco et al (2008) reported that treatment with SDPP during a shortened dry period of about 42 d did result in greater milk yield relative to cows on LDPP. Indeed, the SDPP cows in the study of Velasco et al (2008) averaged 35 d dry despite the target of 6 wk dry.…”
Section: Photoperiod and Lactationmentioning
confidence: 94%
“…However, Velasco et al (2008) reported that treatment with SDPP during a shortened dry period of about 42 d did result in greater milk yield relative to cows on LDPP. Indeed, the SDPP cows in the study of Velasco et al (2008) averaged 35 d dry despite the target of 6 wk dry. Thus, SDPP during the dry period improve milk yield in the next lactation in ruminants, and that effect takes between 35 and 60 d to be fully expressed.…”
Section: Photoperiod and Lactationmentioning
confidence: 94%
“…The increased mesor and greater AUC of melatonin in PS versus CTR cows supports that PS cows had greater daily exposure to melatonin. The increase in milk yield due to exposure to a short-day photoperiod during the nonlactating dry period is also associated with greater circulating melatonin levels (Velasco et al, 2008;Dahl et al, 2012), suggesting that there may be a relationship between melatonin concentrations and milk yield. However, feeding melatonin to increase plasma concentrations did not increase milk yield (Lacasse et al, 2014).…”
Section: Circadian Disruption Changed Rhythms Of Body Temperature Mementioning
confidence: 99%